Is transition experience enough? The donor-side effectiveness of Czech and Polish democracy aid to Georgia. Issue 4 (19th May 2018) - Szent-Iványi, Balázs; Végh, Zsuzsanna
ABSTRACT: The article examines the democracy aid practices of the Czech Republic and Poland in Georgia. These two countries have recently emerged as promoters of democracy, and have argued that their own transition experience puts them in a unique position to support democratization and the consolidation of democracy in the European Union's eastern neighbourhood. The article evaluates how these two countries provide democracy aid to Georgia along three criteria, derived from the aid effectiveness literature: supporting locally driven change, learning from results, and coordination. The results indicate that both countries have plenty of space to improve the way their democracy aid is delivered. Neither country has formal systems in place to ensure that they actually support Georgian priorities; evaluations are ad hoc and feedback loops missing; and there is significant scope to improve coordination with other donors. Nonetheless, there seems to be a general perception among stakeholders that the democracy aid provided by the Czech Republic and Poland is relevant to Georgia's needs.